Field notes contributed by Ione Getscher, winter 1981-1982 - Getscher, Ioneet al (1981)
Field notes were contributed by Ione Getscher. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed